Metastatic bone disease: A review of survival, prognostic factors and outcomes following surgical treatment of the appendicular skeleton. Issue 12 (December 2016) - Kirkinis, M.N.; Lyne, C.J.; Wilson, M.D.; Choong, P.F.M.
Abstract: Survival data and prognostic factors may help to provide insight when deciding on the appropriate orthopaedic treatment for patients presenting with metastatic bone disease. This review was conducted to look at the outcomes following orthopaedic surgery for metastatic lesions in the extremities. The literature was identified through the Medline and Embase database and further refined via a set of inclusion and exclusion criteria. Overall, patients presenting with metastatic bone disease from renal cell cancer or breast cancer had the longest survival rate. Important factors found to predict prognosis was the presence of visceral metastasis, multiple metastases, pathological fracture and the type of primary tumour involved. These prognostic factors may help to direct future inquiry into metastatic bone disease and help determine the type of surgery to use in a metastatic setting in order to avoid complications and unnecessary revisions as well as provide durability.